Determinación de la predecibilidad de trazas de tráfico mediante análisis de recurrencia - Vega Stavro, José Felix; Alzate Monroy, Marco Aurelio (Ingeniería, 2008)
This is one of a series of papers, appearing on this journal, about self-similar traffic characterization. This time we present recurrence analysis techniques their predictability. This is a preliminary result of an ongoing research work on complexity, chaos and fractality in communication networks.